PENGEMBANGAN RUMPUT BRACHIARIA HUMIDICOLA PADA LAHAN PASCA TAMBANG SEMEN DI PT. INDOCEMENT TUNGGAL PRAKARSA - P.D.M.H. Karti; E.B. Laconi; B. Adipradana (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Impact of Mining Operations that can remove some parts of the vegetation, destroying most of the original ecosystem, increase the rate of erosion and runoff, reducing the biodiversity of native species, environmental destruction and wildlife, watershed degradation and unprofitable to support plant growth. Post-mining land must be done reclamation on the ground and then followed by revegetation. The study was conducted in February to June 2009 in Indocement Tunggal Prakarsa company. The design was used is a completely randomized Design Group with four treatments and three replications. The first treatment is without fertilizers (A), the second is adding of manure (B), the third treatment with artificial fertilizers (C), and manure combination with artificial fertilizers treatment (D). Data were analyzed using variance analysis (ANOVA), and if there is a significantly different followed by Duncan multiple range test. Variables have been observed were a number of primary and secondary tiller, production of the primary and secondary tiller, root and shoot dry weight production and absorption of N, P and K. The results showed on the first and second harvest in the treatment D showed significantly different (P <0.05) can increase the number of primary and secondary tillers, the length of spreading, dry weight production and uptake of N, P and K. Treatment D on the first and second harvest showed the optimal results compared with other treatments, although in some variables that are not significantly different with C and B, while A showed the lowest results. This proves that the fertilizer can improve soil fertility in the long term. D treatment is recommended in the development of pasture for Livestock Breeding Center and Incubator Lamb in Indocement Tunggal Prakarsa company.